Circulation Space in the Library Reading Room of University of Lampung - Neneng Widiana Fitri; Ai Siti Munawaroh (Jurnal Linears, 2020)
University of Lampung (Unila) is the first and oldest public university in Lampung Province, having a Library Technical Implementation Unit (UPT) with a centralized library system. As one type of public space, UPT Unila library is the most widely visited place as a place to find references or others. The number of library visitors who carry out activities will affect the comfort of each user's circulation. The purpose of this study was to determine the user's circulation in the library reading room. The method used is descriptive qualitative. Data obtained through the depiction of a floor plan, measurement of the distance between furniture and the area of the room using a meter. The analysis is done by comparing the measurement results with the standard of circulation. The results showed that the circulation in the library reading room of the University of Lampung has not approached the distance in accordance with the standards. The distance between the reading tables in the reading room is less than the standard, while the distance of traffic between the bookshelf and the reading table exceeds the recommended standard.